Teaching physiotherapy in women´s health in public Higher Education Institutions in Brazil (Research, Society and Development, 2022)
The purpose of this study was to describe the scenario of Physiotherapy in Women's Health in public Higher Education Institutions in Brazil. An exploratory cross-sectional study based upon public domain data was conducted. The guiding documents for data collection were the Course Pedagogical Project, course curriculum, teaching plan, course syllabus, or name and content of taught disciplines. Fifty-two Physiotherapy public courses were identified, and 51 (98%) offer a theoretical-practical discipline in Women´s Health. The academic load of Women´s Health was superior in comparison with the mean academic load of the compulsory disciplines (MD 26 hours; 95% CI 14 to 37) and the mean academic load of the applied disciplines (MD 11 hours; 95% CI 2 to 20), but had a high variation among Institutions (45 to 250 hours). Half of the institutions do not offer internship in Women´s Health or do not report whether is offered. Among Institutions that offer, the academic load in Women´s Health is inferior in comparison with the mean academic loads of the other physiotherapeutic specialties (MD -38 hours; 95% CI -61 to -14). The mean difference of the internship academic load was correlated with the total academic load (r=0.38, p=0.04) and with the academic load of the theoretical-practical discipline in Women´s Health (r=-0.44, p=0.02). Thoughts and discussions with members of the Course Collegiate regarding the importance of Physiotherapy in Women´s Health are needed, as well as an updated of the Course Pedagogical Project in order to reflect the scientific advances and the acknowledgement of the discipline in Brazil.